If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + -8(-2w + -6) = 0 Reorder the terms: 3w + -8(-6 + -2w) = 0 3w + (-6 * -8 + -2w * -8) = 0 3w + (48 + 16w) = 0 Reorder the terms: 48 + 3w + 16w = 0 Combine like terms: 3w + 16w = 19w 48 + 19w = 0 Solving 48 + 19w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + 19w = 0 + -48 Combine like terms: 48 + -48 = 0 0 + 19w = 0 + -48 19w = 0 + -48 Combine like terms: 0 + -48 = -48 19w = -48 Divide each side by '19'. w = -2.526315789 Simplifying w = -2.526315789
| x-1+2+3x=6+3 | | aby=c | | 4a*(-3a)= | | f(12)=7x+9 | | 3x+1=x-1+2 | | f(3)=7x+9 | | 10(5+2y)= | | 3x+4-2x=-2 | | f(x)=7x+9 | | 48=5n-2 | | 16c-112=-8+8 | | .5x-4=.67 | | x-2+2x=5x+2 | | a-5/a+5=1 | | 5-0.4g=.5g-4 | | -8+-4(2t+-4)= | | X+-6x=-7 | | 3f*5r= | | 7(v-6)=9v-28 | | 2x(5)=(2) | | 5(-3-9x)+5x=34+9x | | 3(4x+3)+32=15x+7-3x+34 | | x+21+2x=-5-2x-9 | | (7p+4)8=3 | | 4(3x+2-2x+2)=20 | | -2x+21=10 | | 7x-y=14(z) | | 2.1=.8-1z | | 8v-16=2(v-2) | | 2xln(5)=ln(2) | | 2(5+5g)= | | p+0.05p=178.5 |